LOFAR Observations of Shocks in the Solar Corona - Maguire, Ciara (Trinity College Dublin. School of Physics. Discipline of Physics, 2022)
The Sun can produce large-scale energetic events such as solar flares and coronal mass ejections, which can excite shock waves that propagate from the low solar atmosphere into interplanetary space. Such shocks can result in electron acceleration and intense bursts of radio emission known as type II radio bursts. These accelerated particles can cause a variety of potentially dangerous space weather effects, including interruptions or fatal damage to telecommunication satellites and the risk of dangerous doses of particle radiation for astronauts and passengers on commercial aircraft. Hence there is a need to study and understand the physics responsible for shock initiation and propagation in the solar atmosphere. In my PhD, I used the latest observational ground and space-based technologies to study shock signatures and their associated radio emission. I began with a study of the early-phase evolution of shock properties and their relationship to type II burst emission. This was followed by an investigation into the precise origin of a coronal shock, which also involved examining the effects of scattering on fundamental radio emission. Lastly, I investigated a multi-lane type II burst and its relationship to a complex solar eruption. The work described in this talk has provided new insight into shock formation and propagation and how electron acceleration and radio emission are generated during these processes.
APPROVED
Keywords: Interferometry; Solar Physics; Radio Astronomy